2022
DOI: 10.1142/s1363919622500281
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Influence of Environmental Turbulence on Firm Innovation Performance in Emerging Markets: Using an Environment-Strategy-Performance Framework

Abstract: Evidence suggests that turbulent environment exposure is a significant driving force for business innovation. The automotive industry is strongly influenced by environmental dynamics due to continuous technological changes. Car OEMs require an accurate landscape of industrial uncertainties. The purpose of this study is to investigate the role of business environmental turbulence (BET) in innovation performance. Applied to the environment-strategy-performance framework and underpinned by the dynamic capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 99 publications
2
2
0
Order By: Relevance
“…Thus, our study contributes to the theory by showing the bright side of environmental uncertainties and how they help managers in mature and entrepreneurial firms become aware of the importance of developing NCs. We confirm the findings of Mokhtarzadeh et al . (2022), which showed that business environment turbulence and how managers perceive it improve innovation performance through enhancing NCs and collaborative innovation capability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, our study contributes to the theory by showing the bright side of environmental uncertainties and how they help managers in mature and entrepreneurial firms become aware of the importance of developing NCs. We confirm the findings of Mokhtarzadeh et al . (2022), which showed that business environment turbulence and how managers perceive it improve innovation performance through enhancing NCs and collaborative innovation capability.…”
Section: Discussionsupporting
confidence: 93%
“…During crises, relationships must be managed differently to ensure efficient resource exchange while controlling the risks associated with firms' interdependencies (Zafari et al ., 2020). Therefore, our results confirm previous studies arguing that environmental conditions can be a driving force acting on NCs (Mokhtarzadeh et al ., 2022). The findings also indicate that NCs are important organizational assets during difficult times when firms are exposed to environmental uncertainties.…”
Section: Discussionsupporting
confidence: 92%
“…Enterprises must assess and adjust their organizational boundaries based on the environment's dynamism to adapt to changing transaction conditions [46]. This study considers environmental turbulence as an influencing factor in corporate symbiotic relationships [47]. Research related to influencing factors primarily involves environmental turbulence and technological turbulence.…”
Section: Environmental Turbulence and Frugal Innovationmentioning
confidence: 99%
“…This characteristic is often associated with rapid transformations and high uncertainty. In research conducted by Mokhtarzadeh et al [47], environmental turbulence is further divided into two dimensions: market turbulence and technological turbulence. Following the approach of Jansen et al [58], we devised a five-item scale to measure technological turbulence and another five-item scale to capture market turbulence.…”
Section: Variable Measuresmentioning
confidence: 99%